Podmiotowość w opiece realizowana w placówkach katolickich - Opiela, Maria Loyola (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The realization of the principle of subjectivity in care has its specific scope in the activities carried out in Catholic institutions. Defining care as a service of love indicates interpersonal relationships in its fulfillment, basing motivation on the commandment of love. Consideration of this reference obliges to maintain all standards, both in exercising care with respect for the dignity of each person, the high quality of its activities, as well as the requirements of applicable law. In this process, there is a full development of its entities in the mutual exchange of values and services tailored to individual needs and possibilities.